Маяковский Вл.: биография: пособие для учащихся / С. В. Владимиров, Д. М. Молдавский - Владимиров Сергей Васильевич (Просвещение, 1974)
Экземпляры: Селтинская районная библиотека (аб) (20221025) / Инвентарный номер: 861 / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: В 57 / ГРНТИ: 17 / ББК: 83.3(2Рос=Рус)6